Antidiabetic Potential of Emodin in Streptozotocin-Induced Type-2 Diabetic Rats Evaluating the security and privacy of pharmacy-based electronic health records - Gurudiwan, Prachi; Kumar Sahu, Mahendra (Journal of Neonatal Surgery, 2025)
The phrase "cloud computing" refers to a new technology that allows users to store data remotely. Data privacy, data sharing, and keyword searching in encrypted data are the main problems with cloud computing that cloud users face. Effective data exchange and privacy protection are lacking in the current cloud platform solutions. Additionally, it is necessary to increase the effectiveness of different techniques with the present technical audits. However, it results in issues with traceability and freshness of data while maintaining privacy. Privacy-Preserving Data Mining (PPDM) is a new field with privacy concerns and a lot of fresh work being done. The Cloud is the most cutting-edge technology available in the digital world for storing enormous amounts of Internet data. One of the real-time outsourcing strategies for storing Internet data on the cloud is cloud computing. The cloud is where a vast amount of Internet data can be gathered. Data access is possible anywhere, at any time, and with minimal effort and unreal resources (e.g., different apps, software systems, hardware systems, and progressive operating environments). The operational settings and applications are modified and redesigned based on the type of data, allowing for the optimal use of the environment and verifying a variable burden. While reliability depends on the service provided by the flexible service level approach, implementation is dependent on the surrounding environment and other pertinent competencies.